Pseudo-steroid resistant asthma. Issue 4 (1st April 1999) - Thomas, Paul S; Geddes, Duncan M; Barnes, Peter J
Abstract : BACKGROUND: Steroid resistant asthma (SRA) represents a small subgroup of those patients who have asthma and who are difficult to manage. Two patients with apparent SRA are described, and 12 additional cases who were admitted to the same hospital are reviewed. METHODS: The subjects were selected from a tertiary hospital setting by review of all asthma patients admitted over a two year period. Subjects were defined as those who failed to respond to high doses of bronchodilators and oral glucocorticosteroids, as judged by subjective assessment, audible wheeze on examination, and serial peak flow measurements. RESULTS: In 11 of the 14 patients identified there was little to substantiate the diagnosis of severe or steroid resistant asthma apart from symptoms and upper respiratory wheeze. Useful tests to differentiate this group of patients from those with severe asthma appear to be: the inability to perform reproducible forced expiratory manoeuvres, normal airway resistance, and a concentration of histamine causing a 20% fall in the forced expiratory volume (FEV1 ) being within the range for normal subjects (PC20 ). Of the 14 subjects, four were health care staff and two reported childhood sexual abuse. CONCLUSION: Such patients are important to identify as they require supportive treatment which should not consist of high doses of glucocorticosteroids and β2 adrenergic agonists. Diagnoses other than asthma, such as gastro-oesophageal reflux, hyperventilation, vocal cord dysfunction and sleep apnoea, should be sought as these may be a cause of glucocorticosteroid treatment failure and pseudo-SRA, and may respond to alternative treatment.